Impaired glymphatic system function and its association with speech and language delay in children with ADHD: a prospective study - Li, Yangchen; Wang, Jianhong; Yuan, Xinyu; Zhang, Lili; Yan, Yuchun; Yang, Yang; Wang, Lin (Frontiers in Human Neuroscience, 2025)
ObjectiveThe glymphatic system, a glial cell-dependent waste clearance pathway in the brain, is essential for the maintenance of brain homeostasis. This study aimed to explore the relationship between attention-deficit/hyperactivity disorder (ADHD) and its co-occurring clinical phenomena, including gross motor and language development, and the glymphatic system.MethodsA total of 56 children with ADHD and 33 age-and gender-matched typically developing (TD) children were included in this prospective study. Diffusion tensor image analysis along the perivascular space (DTI-ALPS) was used to calculate the ALPS index, which evaluates glymphatic system function. The ALPS index of ADHD patients was compared with that of TD, and the correlation between the gross motor retardation and speech and language delay in ADHD patients and ALPS index was further analyzed.ResultsThe ALPS index in ADHD patients was significantly lower than that in TD children (1.503 ± 0.153 vs. 1.591 ± 0.152, p < 0.05). After adjusting for age and sex, the ALPS index was negatively correlated with speech and language delay in ADHD patients (r = −0.329, p = 0.015). However, no significant correlation was found between the ALPS index and gross motor retardation in ADHD patients.ConclusionGlymphatic system function may be impaired in ADHD patients. This study is the first to demonstrate that speech and language delay in ADHD patients may be associated with impaired glymphatic system function. Early intervention may be linked to better language trajectories in ADHD, providing a rationale for longitudinal trials to test causality.